Perspective of Gene Therapy for Regenerative Medicine: The Future of Complex Disease and Regenerative Application - Deby Susanti Pada Vinski; Darren Griffin; Svetlana Trofimova; Natasha Cinta Vinski; Elizabeth Parish (Riviera Publishing, 2025)
Recent breakthroughs in biotechnology have significantly advanced the potential to regenerate damaged human tissues. Innovations in stem cell science, genetic engineering, and tissue scaffolding have rapidly pushed the boundaries of regenerative medicine. Yet, numerous technical hurdles remain, particularly concerning the clinical application of gene therapy. Core objectives of gene therapy include enhancing protein synthesis within cells, suppressing overactive genes, and rectifying dysfunctional cellular mechanisms linked to disease. While viral vectors remain dominant in current clinical trials due to their effectiveness, they carry risks of immune reactions and pathogenicity. This has sparked increased interest in non-viral alternatives, which promise greater safety and versatility. Non-viral delivery methods utilize plasmid DNA systems and synthetic carriers to transport therapeutic genes and show great potential, especially when integrated with tissue engineering techniques. By combining these non-viral tools with regenerative approaches, researchers aim to more precisely control the spatial and functional behavior of introduced genes within the body. This review critically assesses the evolution and challenges of gene therapy within the broader scope of regenerative medicine, with an emphasis on emerging non-viral delivery systems and their translational promise.